A snapshot of the limnological features in tropical floodplain lakes : the relative influence of climate and land use - Alves, Maria Tereza Ribeiro (2019)
Aim This study aimed to investigate the relative influence of climate (temperature and precipitation) and land use on limnological features of 30 floodplain lakes in the Araguaia River, in Central Brazil, an important river that drains in the Brazilian Cerrado. Methods The lakes were sampled in one same period, at a large spatial scale (900 km along the river) covering climate and landscape variability. For decomposing the relative importance of land use and climate, we used the RDA and partitioning variance techniques. Results The lakes presented limnological gradient along the floodplain; in general, the lakes presented low transparency, nutrients concentrations ​​(total nitrogen and total phosphorus) and oxygen saturation. The water pH was considered weakly acidic. Considering land use in Araguaia river basin, lakes in downstream presented more remnant vegetation and lakes in upstream presented more livestock and agriculture soil use. The climate conditions were the most important in explaining the variation in limnological characteristics of the lakes, while the individual analysis of limnological variables showed that land use was important to explain to the pH and transparency of the water. Conclusions Finally, this study showed the importance of investigating regional climatic attributes and land use information to explain the limnological characterization of floodplain lakes. Thus, it highlights the importance of the possible impacts of global climate change on limnological conditions.